EFL learners’ phonemic awareness: A correlation between English phoneme identification skill toward word processing - Rokhman, Miftakh Farid; Lintangsari , Alies Poetri; Perdhani, Widya Caterine (JEES (Journal of English Educators Society), 2020)
This research aims to find out the correlation between English phoneme identification skills and word processing. It applies the quantitative approach with correlation design. The participants are 100 of 3rd- semester students in English Language Education Program. The correlational result reveals that it has correlation with .382 degrees in phoneme identification skill toward blending skill with the significance level .000, and .359 degrees in phoneme identification skill toward segmentation skill with the significance level .000. Then, the correlation result of English phoneme identification skill toward word processing is .462 degree with its significance .000. By the result, awareness to identify phoneme by initial, medial, and final sound correlates to the blending and segmenting skills which influence the comprehension of word. The more the students are able to identify phoneme based on its sound, the more the students will be able to blend and segment phoneme. Lastly, the ability to identify English phonemes is proven to be a skill that supports EFL learners on their productive and receptive skills. Then being able to identify its phonemes will assist on recognizing and processing English words appropriately so that English language teaching can be associated with the use of phoneme-based instruction on its teaching process. Highlights : Ability to identify English phonemes is proven to be a skill that supports EFL learners on their English productive and receptive skills. English phoneme identification skill contributes to blending and segmentation skill since phonemic awareness provides both decoding and encoding skill.